Obesity‐related asthma in children: A role for vitamin D. Issue 2 (8th December 2020) - O'Sullivan, Brian P.; James, Laura; Majure, Joseph M.; Bickel, Scott; Phan, Ly‐Thao; Serrano Gonzalez, Monica; Staples, Heather; Tam‐Williams, Jade; Lang, Jason; Snowden, Jessica; ,
Abstract: Excess adipose tissue predisposes to an enhanced inflammatory state and can contribute to the pathogenesis and severity of asthma. Vitamin D has anti‐inflammatory properties and low‐serum levels are seen in children with asthma and in children with obesity. Here we review the intersection of asthma, obesity, and hypovitaminosis D in children. Supplementation with vitamin D has been proposed as a simple, safe, and inexpensive adjunctive therapy in a number of disease states. However, little research has examined the pharmacokinetics of vitamin D and its therapeutic potential in children who suffer from obesity‐related asthma.